Metapolitical seduction: Women's language and white nationalism - Tebaldi, Catherine (Journal of Linguistic Anthropology, 2024)
This paper examines the enregisterment of white nationalist women's language as metapolitical seduction, in anti-feminist conversion videos designed both to seduce men and to restore them to their proper place—above women. First, the paper analyzes the metapragmatics of submissive femininity, then the characters this far right fairy tale invents, and finally how they come to represent a metapolitical order which aligns gender, nation, tradition, and language. Women's language contributes to the white nationalist metapolitical project of resurrecting white masculinity and re-gendering the world, also revealing mechanisms by which white supremacy is made to appear not only normal, but desirable.
Keywords: 2000 à aujourd'hui; 2010-2019; antiféminisme; approches et analyses; cours; discipline; discours médiatique; histoire et politique; internet; lin2685; linguistique; premier cycle; périodes historiques; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; trad wife

Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; discipline; genre; intersectionnalité; linguistique; montréal; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; étude qualitative